(untitled) (ModaPalavra e-periódico, 2023)
This article investigates the noble feminine clothing from the Rio de Janeiro court, at the beginning of the 19th century, based on Jean- Baptiste Debret ́s watercolors. Due to the great dimension of this artist’s work, 5 finished watercolors were selected, belonging to Castro Maya Collection, in which it is possible to explore the details of the costumes. The academic basis embranced in the argumentative construction of the text is based on the premise that the social fabric can be understood, among other elements, from clothing and fashion. Thereby, in the perspective of a Social History of clothing, it analyzes how the Portuguese dress influenced the elaboration of the clothing used by the ladies from local elites, which makes it possible to understand how the values of the European civilization are disseminated and incorporated by the society of Rio de Janeiro, starting from the creation of a new clothing aesthetic.